Endoscopic Approaches to the Treatment of Variceal Hemorrhage in Hemodialysis-Dependent Patients - Xiaoquan Huang; Lili Ma; Xiaoqing Zeng; Jian Wang; Jie Chen; Shiyao Chen (Gastroenterology Research and Practice)
Background. Esophagogastric variceal hemorrhage leads to challenging situation in chronic kidney disease patients on maintenance hemodialysis. Aims. To determine the safety and efficacy of endoscopic approaches to patients with hemodialysis-dependent concomitant with esophagogastric varices. Methods. Medical records were reviewed from January 1, 2004, to December 31, 2015, in our hospital. Five consecutive hemodialysis-dependent patients with variceal hemorrhage who underwent endoscopic treatments were retrospectively studied. Results. The median age of the patients was 54 years (range 34–67 years) and the median follow-up period was 21.3 months (range 7–134 months). All the patients received a total of three times heparin-free hemodialysis 24 hours before and no more than 24 hours and 72 hours after endoscopic treatment. They successfully had endoscopic variceal ligation, endoscopic injection sclerotherapy, and/or N-butyl cyanoacrylate injection. The short-term efficacy is satisfying and long-term follow-up showed episodes of rebleeding. Conclusions. Endoscopic approaches are the alternative options in the treatment of upper gastroenterology variceal hemorrhage in hemodialysis-dependent patients without severe complications.